IMPLEMENTASI, PELATIHAN, DAN SOSIALISASI PENGGUNAAN SISTEM INFORMASI DATABASE OAIL - Eko Dwi Nugroho; Aidil Afriansyah; Miranti Verdiana; Radhinka Bagaskara; Muhammad Habib Algifari; Winda Yulita; Mugi Praseptiawan (Universitas PGRI Yogyakarta, 2022)
Space phenomena are natural events that are rarely seen by humans and are still a lot of mysterious and interesting things to observe and study. In Indonesia, there are still few places to observe and study space phenomena. The Sumatran Institute of Technology (ITERA) has a technical implementing unit as well as a study program related to space. The units are the Lampung ITERA Astronomical Observatory Unit (UPT OAIL) and the Atmospheric and Planetary Science Study Program. However, these units and study programs do not yet have an information system that can store various space data and display them, especially for the public to see. This is the background for us to do community service for lecturers and students in the form of making the OAIL database system. The information system can be used to store space data to be studied and can be seen by the public. The form of the system is website-based so that people throughout Indonesia, especially on the island of Sumatra, can see various space phenomena. For three months, the information system was successfully created and can be implemented by UPT OAIL, so that this community service activity went according to plan and well. It is hoped that the information system can always be developed and useful for the benefit of learning at ITERA and the community. Keywords: space, database, OAIL, astronomical observatory, information system.